Radiation chemistry in astrochemical models: From the laboratory to the ISM. Issue Volume 15:Issue S350(2019) (April 2019) - Shingledecker, Christopher N.; Ivlev, Alexei; Kästner, Johannes; Herbst, Eric; Caselli, Paola
Abstract: Most interstellar and planetary environments are suffused by a continuous flux of several types of ionizing radiation, including cosmic rays, stellar winds, x-rays, and gamma-rays from radionuclide decay. There is now a large body of experimental work showing that these kinds of radiation can trigger significant physicochemical changes in ices, including the dissociation of species (radiolysis), sputtering of surface species, and ice heating. Even so, modeling the chemical effects that result from interactions between ionizing radiation and interstellar dust grain ice mantles has proven challenging due to the complexity and variety of the underlying physical processes. To address this shortcoming, we have developed a method whereby such effects could easily be included in standard rate-equations-based astrochemical models. Here, we describe how such models, thus improved, can fruitfully be used to simulate experiments in order to better understand bulk chemistry at low temperatures.